Fosfomycin Versus Nitrofurantoin Efficacy Against Multi-Drug Resistant Gram Negative Urinary Pathogens. - , Nadia Wali , Tariq Butt , UsmanWali , Zakir Hussain (Journal of Rawalpindi Medical College, 2018)
Background: To compare antimicrobial susceptibility pattern of fosfomycin and nitrofurantoin against multi-drug resistant gram negative uropathogens. Methods: In this descriptive study identification of 200 isolates of gram negative bacteria was done by using standard microbiological techniques and the antimicrobial susceptibility was carried out by employing Kirby-Bauer disc diffusion technique. The susceptibility pattern of isolates was then recorded in frequency and percentages. Results: Out of total 200 urinary samples, 97 were multi-drug resistant (MDR) and 103 were non multi-drug resistant gram negative bacteria. Both MDR and non MDR Escherichia coli(E. coli) followed by Klebsiella pneumoniae(K. pneumoniae) were more commonly isolated uropathogens. MDR E. coli was more susceptible to fosfomycin (98%) as compared to nitrofurantoin (81%). Similarly, for MDR K. pneumoniae, same results of better susceptibility of fosfomycin as compared to nitrofurantoin were observed. Maximum resistance was observed in 4 to 5 drugs in MDR E.coli and K. pneumonia and the most predominant resistant pattern was observed in ampicillin and cephalosporins . Conclusion: Fosfomycin holds much better in vitro efficacy as compared to nitrofurantoin against MDR E. coli, K. pneumoniae and P. stuartii.